The Effectiveness of giving some type of Mycorrhizae to Osmoregulation Rubber Plant In the Land with DroughtStress that has given an Organic Matter In Aek Godang village, Sihapas Hulu, North Padang Lawas - Amir Mahmud Manurung; Asmarlaili Sahar; Hardy Guchi (Jurnal Agroekoteknologi, 2018)
Rubber (Hevea brasiliensis Muell. Arg) is one of the superior plantation commodities that has a huge potential in Indonesia. Rubber development is centered on the areas with rainfall 2500-4000 mm / year. In that area the rubber faces a lot of land competition issues and also the disease that need to maximize the potential of the low annual rainfall area. This research was conducted on citizen plantations in  Aek Godang village, Sihapas Hulu, North Padang Lawas , on March-April 2016, aimed to test the influence of giving mycorrhiza to Osmoregulation PB260 clone rubber seedlings on lands with drought stress that has given an organic matter. This research using random sampling in non-factorial, with mycorrhiza treatment with M symbol that consists of 3 levels ; M0 = without mycorrhiza, M1 = Acaulospora 100g / plant,M2 = Glomus + Acaulospora (1: 1) 100g / plant, with each level of treatment has 9 reiteration. The Variables observed were consist of leaf water potential, osmotic pressure and turgor pressure. The results showed that the distribution of mycorrhiza has a significant effect on the improvement of leaf water potential, but it has no a significant effect on the improvement of turgor pressure of rubber plant.